Delayed diagnosis in Vitamin D – dependent rickets type II results in severe skeletal deformities - Sohail, Erum; Ahsan, Tasnim; Jabeen, Rukhshanda; Rehman , Urooj Lal; Ghaus, Saima (Journal of the Pakistan Medical Association, 2022)
Vitamin D-dependent Rickets Type II (VDDR-II) is a rare autosomal recessive disorder caused by a vitamin D receptor gene mutation, leading to end-organ resistance to 1,25-dihydroxyvitamin D 1,25(OH)2D. We aimed to investigate two cases of VDDR-II. Case 1 was of a 14-year old male, presenting with bone pains, bowing of legs, multiple bone deformities, and fractures since childhood. On examination, Chvostek’s and Trousseau’s signs were positive, and there was no alopecia. Case 2 was a 15-year old male who presented with pain in both legs since childhood and difficulty in walking lately. Upon investigation, it was found that bowing of legs, and Chvostek’s and Trousseau’s signs were positive. Both cases had severe hypocalcaemia, normal/low phosphate levels, and high alkaline phosphatase (ALP). —Continue